The Effect Of Peer Group On Sexual Behavior Of Adolescent In High School State Vocational School 1 Pagerwojo Tulungagung - Putri Eka Sejati; Tanti Rahma Olimpia (Universitas STRADA Indonesia, 2023)
Peer group or peer group is a source of affection, sympathy, understanding, and moral guidance as well as a setting to gain autonomy and independence from parents. Peers are friends of the same age with closeness and a sense of belonging. School-age children focus on the rules of friends, but parents are still influential in directing children. This study aimed to determine the influence of peer groups on the sexual behavior of tenth graders in the State Vocational High School 1 Pagerwojo Tulungagung. Methods This research is analytical research with a pre-experimental approach. The sample in this study was 30 students and class X students. Data analysis used paired samples T-test. Based on the results of statistical tests, it was obtained that the value of p = 0.000 <0.05. So that there is an influence of Peer-Group on the sexual behavior of class X teenagers in the State Vocational High School 1 Pagerwojo Tulungagung. This study concludes that in the Peer-Group group, most of the respondents have sexual behaviour, which is 12 respondents (70%). Meanwhile, students who did not join Peer-Group showed that most respondents had no sexual behaviour, namely nine respondents (60%). Suggestions for adolescents It is necessary to make efforts to equip themselves with various knowledge, especially about adolescent reproductive health, and not abuse participating in extra-curricular activities at school to behave sexually and be active in seeking reproductive health information at school or independently using the internet facilities with assistance and supervision from teachers or parent.